Unraveling the mystery: Giant left atrial myxoma neovascularization through the right coronary artery - Digvijay Nalawade; Vijay Sharma; Kriti Soni; Harika Chhabra; Ankit Shokeen (Heart India)
Primary cardiac tumors are exceedingly rare, with an incidence ranging from 0.001% to 0.03% in autopsy studies. Among these, cardiac myxomas are the most common in adults, representing approximately half of all benign cardiac tumors. A retrospective study at the mayo clinic, involving 323 patients who underwent surgical resection of primary cardiac tumors between 1957 and 2006, revealed that 94% of these tumors were benign, with myxomas accounting for 50% of the cases. Myxomas predominantly occur in the atria, particularly in the left atrium. Although patients with myxomas may be asymptomatic, they can present with a triad of symptoms: embolism, intracardiac obstruction, and constitutional symptoms. The latter, which include low-grade fever, malaise, and decreased appetite, is attributed to the gradual release of inflammatory cytokines such as interleukin (IL)-1, IL-6, and tumor necrosis factor-alpha from the tumor. Understanding the vascularity of the tumor is crucial for surgeons, as knowing the blood supply and vascular territory can help minimize and control blood loss during surgery.